CT Findings in Acute, Subacute, and Chronic Ischemic Colitis: Suggestions for Diagnosis. (27th August 2014) - Iacobellis, Francesca; Berritto, Daniela; Fleischmann, Dominik; Gagliardi, Giuliano; Brillantino, Antonio; Mazzei, Maria Antonietta; Grassi, Roberto
Abstract : Purpose . This paper aims at evaluating CT findings of occlusive and nonocclusive ischemic colitis (IC), in correlation with the etiology and the different phases of the disease. Materials and Methods . CT examination and clinical history of 32 patients with proven IC were retrospectively reviewed. The CT findings were analyzed according to the different phases of the disease (acute, subacute, and chronic). Results . Among the 32 CT examinations performed in the acute phase, 62.5% did not present signs of occlusion of the superior mesenteric artery (SMA) or inferior mesenteric artery (IMA), whereas IMA occlusion was detected in 37.5% of CT examinations. In the acute phase, the presence of pericolic fluid was found in 100% of patients undergoing progressive resorption from acute to subacute phase if an effective reperfusion occurred; the bowel wall thickening was observed in 28.1% patients in acute phase and in 86.4% patients evaluated in subacute phase. The unthickened colonic wall was found in all conditions where ischemia was not followed by effective reperfusion (71.9% of cases), and it was never found in chronic phase, when the colon appeared irregularly thickened. Conclusion . CT allows determining the morphofunctional alterations associated with the IC discriminating the occlusive forms from the nonocclusive forms. CT, furthermore, allows estimating the timing of ischemic damage.